Evaluation Of Epithelization When Amniotic Membrane Use As A Biologic Dressing In Oral Cavity (Update Dental College Journal, 2018)
Background:Skin act as a protective barrier to prevent the contamination from environment and dehy- dration of tissue. After any surgery to the oral cavity, wound closure or reconstruction is mandatory which is done by skin graft and skin substitute like amniotic membrane by the process of epithelializa- tion and tissue regeneration. Amniotic membrane is use as skin substitute in burn, eye and oral cavity as biologic wound dressing.Objective:To evaluate the epithelialization after use of amniotic membrane in mucosal defect of oral cavity as a biologic dressing.Methods:This was a prospective study which included 26 with premalignant lesion in buccal mucosa who under went excision of the lesion from intraoral buccal mucosa between January 14-june 15 and post operative follow up for 4-6 month after the surgical procedure. We used amniotic membrane(am) for dressing of the defects in buccal mucosa of oral cavity under local anesthesia. Efficacy of this procedure was assessed by granulation tissue formation with surface epithelialization on the graft site.Results:The epithelialization evaluated in postoperative period. According to sex 40 males 70% and 30 females age 22-72 years with means age 45.0±10.5 years. After excision of lesion from buccal mucosa amniotic membrane was grafted on the defect. Completeadherence of amniotic membrane in most of the cases.Wound covered by epithelialization was entire wound coverage in 85% and Nearly entire wound coverage in 15% when use amniotic membrane use as a biologic dressing in oral cavity. No allergic reaction occurs in any patients.Conclusion: Amniotic membrane can be useas a skin substitute in buccal mucosa of the oral cavity.Update Dent. Coll. j: 2018; 8 (1): 36-40